Additive manufacturing technologies : 3D printing, rapid prototyping, and direct digital manufacturing - Gibson, Ian; Rosen, David; Stucker, B. (Springer, 2015)
This book covers in detail the various aspects of joining materials to form parts. A conceptual overview of rapid prototyping and layered manufacturing is given, beginning with the fundamentals so that readers can get up to speed quickly. Unusual and emerging applications such as micro-scale manufacturing, medical applications, aerospace, and rapid manufacturing are also discussed. This book provides a comprehensive overview of rapid prototyping technologies as well as support technologies such as software systems, vacuum casting, investment casting, plating, infiltration and other systems. This book also: Reflects recent developments and trends and adheres to the ASTM, SI, and other standards Includes chapters on automotive technology, aerospace technology and low-cost AM technologies Provides a broad range of technical questions to ensure comprehensive understanding of the concepts covered.- Resumé vydavatel
Keywords: trojrozměrný tisk; automatizované výrobní systémy; CAD/CAM systémy; trojrozměrné modelování; three-dimensional printing; manufacturing technology; automated manufacturing systems; CAD/CAM systems; three-dimensional modelling; aditivní výroba; elektronické knihy; monografie; electronic books; monographs